The number of postoperative surgical or diagnostic procedures following congenital heart surgery correlates with both mortality and hospital length of stay. Issue 10 (2nd August 2022) - Capecci, Lou; Mainwaring, Richard D.; Collins, R. Thomas; Sidell, Doug; Martin, Elisabeth; Lamberti, John J.; Hanley, Frank L.
Abstract: Background: Outcomes for congenital heart disease have dramatically improved over the past several decades. However, there are patients who encounter intraoperative or postoperative complications and ultimately do not survive. It was our hypothesis that the number of postoperative procedures (including surgical and unplanned diagnostic procedures) would correlate with hospital length of stay and operative mortality. Methods: This was a retrospective review of 938 consecutive patients undergoing congenital heart surgery at a single institution over a 2‐year timeframe. The number of postoperative surgical and unplanned diagnostic procedures were counted and the impact on hospital length of stay and mortality was assessed. Results: 581 of the 938 (62%) patients had zero postoperative diagnostic or surgical procedures. These patients had a median length of stay of 6 days with a single operative mortality (0.2%). 357 of the 938 (38%) patients had one or more postoperative diagnostic or surgical procedures. These patients had a total of 1586 postoperative procedures. There was a significant correlation between the number of postoperative procedures and both hospital length of stay and mortality ( p < .001). Patients who required 10 or more postoperative procedures had a median hospital length of stay of 89 days and had a 50% mortality. There were no survivors in patients who had 15 or more postoperative procedures. Conclusions: The data demonstrate that the number of postoperative procedures was highly correlated with both hospital length of stay and mortality.